Identification of the farm of origin of Atlantic salmon smolt escapees in a freshwater Scottish loch using single-nucleotide polymorphic markers. (28th June 2018) - Gilbey, John; Cauwelier, Eef; Sampayo, James; Matejusova, Iveta; Allan, Charles; Graham, Jennifer; Stradmeyer, Lee; Middlemas, Stuart; ,
Abstract: In this article, we present the first use of genetic assignment to determine the origins of farmed Atlantic salmon ( Salmo salar L.) escaping directly into freshwater. Juvenile fish ( n = 220) sampled from rotary screw traps operating on tributaries of Loch Shin in Scotland had characteristics suggesting they were of farm origin (scale losses, fin damage, and vaccination marks). To investigate their origins, baseline samples ( n = 1200) were collected from the two freshwater smolt rearing facilities on the Loch. Baseline analysis with 186 single-nucleotide polymorphic (SNP) markers identified three assignment units associated with the aquaculture strains in production, Mowi and Aquagen at Site A and Fanad at Site B. Exclusion analysis identified at least 37% of the suspected escapees as being of farmed origin, 95% from Site A and 5% from B. The non-random nature of fish collection and trapping locations prevented determination of either absolute proportions of escapees in the entire Shin system or escape proportions from each site. However, it was clear that fish from both sources had escaped. The study demonstrates that genetic assignment to farm origin is possible in a novel situation in which fish have escaped at the smolt stage directly into freshwater.